Socio-Legal Analysis of the Acquittal Verdict in the Food Security Fund Corruption Case in Banjarnegara - Putra, Royce Wijaya Setya (Law Research Review Quarterly, 2025)
The handling of corruption cases in the food security sector has become a public spotlight, especially when the judge at the Corruption Court at the Semarang District Court acquitted the defendant, namely the Secretary of Kaliwinasuh Village, Banjarnegara Regency, Rito. This study analyzes the acquittal in the alleged corruption case of food security funds worth IDR 214,000,000 (two hundred and fourteen million rupiah) in September 2024, using a socio-legal approach. This approach is used to examine not only the legal aspects of the verdict, but also the social, political, and structural contexts that influence the judicial process. The study uses a qualitative method, with court decision document study techniques, and media analysis. The results of the study show that the acquittal was not only based on legal evidence, but was also influenced by weak coordination between law enforcement agencies, inconsistencies in evidence, and social and political pressures in the region. This study concludes that the acquittal in this case reflects the dysfunction of the criminal justice system in handling corruption cases, and has caused a crisis of public trust in the legal process. Therefore, it is necessary to reform the legal approach and strengthen the supervisory system to ensure accountability in corruption cases related to the public interest.